Propuesta de diseño detallado de una máquina lavadora y clasificadora adaptada a las necesidades de la producción de limones en la hacienda San Antonio - Jiménez Cabrera, Andrea Stephanie (2024)
The lemon washing and sorting machine that was designed for the San Antonio farm aims to improve the quality of the final product, for a capacity of 150 kg per cycle, with lemon refill intervals every 20 minutes, achieving a total processing capacity of 450 kg/h. To do this, a system was designed that allows washing, drying and sorting lemons according to: diameter, prioritizing the sizes most in demand by the market. The system works with a single-phase 220 V electrical supply and requires a single operator to operate. Additionally, corrosion-resistant materials were used to ensure the durability of the machine. The system is made up of three main areas: the washing area, the drying area and the sorting area. In the washing area, the lemons are brushed with water at an outlet pressure of 29 PSI using sprinklers connected to a 3 kW pump that removes impurities and residue from the surface. The water is recycled through a tank with a sedimentation and filtering system that prevents waste. In the drying area, the lemons are transported by a belt connected to a 0.12 kW gear motor that exposes them to air generated by three 80 W fans that remove humidity. In the classification area, the lemons are filtered through a metal structure inclined at 20 degrees that separates them according to their size. The investment determined for the construction of the machine was 8189.14 US dollars, including the costs of materials and labor. The estimated annual expense for the operation of the machine, considering one hour of daily use for 180 days a year, plus the cost of preventive maintenance and the operator's salary, was 2089.99 US dollars. Keywords: Lemon sorter, lemon washing machine, draining system, grizzly sieves.